Translation of English film titles into Chinese: a pragmatic and socio-cultural adaptation perspective - Hu, Xiaojing; Abdul Halim, Hazlina; Mohd Zin, Zaid (Sciedu Press, 2025)
Film titles serve as the initial point of engagement between films and their audiences, playing a pivotal role in shaping expectations and supporting promotion efforts. These titles often carry distinct cultural meanings and linguistic nuances that encapsulate the film’s essence, making their translation a complex task requiring creativity and strategic decision-making. Hence, translators need to balance fidelity to the original with sensitivity to the cultural and communicative norms of the target audience. Given its importance, there is a need to explore the features of film titles and the translation strategies. While numerous studies have been given to the translation of film titles from various theoretical standpoints, limited attention has been given to the translation of film titles through the framework of adaptation theory. This paper investigates the translation strategies of English film titles into Chinese through the lens of Volkova and Zubenina’s (2015) pragmatic and socio-cultural adaptation theory. By analyzing selected titles from IMDb and their Chinese counterparts on Douban, the study offers insights into how pragmatic and socio-cultural features shape adaptation strategies, enhancing translators’ awareness in cross-cultural audiovisual translation. This study hopes to contribute to the burgeoning field of titleology by highlighting how adaptation functions at the intersection of translation, culture, and audience engagement. Ultimately, the findings are anticipated to offer practical insights for translators and enrich our understanding of the socio-pragmatic dimensions involved in cross-cultural audiovisual translation.